Evaluation of a Visualization Assay for Blood on Forensic Evidence. Issue 3 (20th February 2015) - Vandewoestyne, Mado; Lepez, Trees; Van Hoofstat, David; Deforce, Dieter
Abstract In forensics, bloodstains on dark fabrics might be invisible for the naked eye. Although several visualization, presumptive, and confirmatory blood tests have been developed, all have one or more disadvantages, especially on DNA analysis. We report here the use of a visualization assay that can visually detect blood drops up to 1/20 dilution. In this assay, the fabric is placed between two wet filter papers and covered by glass surfaces on both sides. Pressure is applied on the glass surfaces in which bloodstains transfer onto the filter papers through capillary forces. Detected stains can be tested with other more sensitive presumptive blood tests performed on the filter paper. Even more, DNA analysis can be performed on the transferred bloodstains. The presented visualization assay is easy to perform, extremely cheap, requires little hands on time, and does not affect bloodstain pattern analysis.